Perancangan Ui/Ux Aplikasi Penjualan Makanan Berbasis Mobile Pada Umkm Angkringan Berkah Menggunakan Metode Design Thinking - M Agus Sajiwo; Randi Rian Putra; Sri Wahyuni (Jurnal Nasional Teknologi Komputer, 2025)
The development of digital technology has brought major changes in various sectors, including the culinary industry and MSMEs. Angkringan Berkah MSMEs face challenges in improving operational efficiency and competitiveness through the application of mobile-based technology. This research aims to design the UI/UX of a mobile-based food sales application with a Design Thinking approach to improve user experience and the effectiveness of digital transactions. The Design Thinking method is applied through the stages of empathy, problem definition, ideation, prototyping, and testing. The results showed that the developed UI/UX design successfully improved the ease of use of the application, accelerated the ordering process, and provided a better user experience. Usability testing showed a high level of satisfaction from users in navigation and interaction with the application. Comparison with previous research confirmed the effectiveness of the Design Thinking method in creating a more intuitive and user-friendly design. Despite some limitations in additional features, this research makes an important contribution to the digitalization of culinary MSMEs. The results of this study can serve as a reference for similar application developers in improving usability and functionality aspects in the future.